Market level characteristic factors influencing smallholder coffee marketers in Kogi State, Nigeria - Akinpelu, A. O.; Okunade, A. F.; Oluyole, K. A. (Recent Research in Science and Technology)
The study assessed the market level characteristic factors influencing coffee marketing among coffee farmers in the study area. The study was carried out in Kogi State and purposive sampling technique was used to select eighty four respondents. Data were collected from the respondents with the use of structured questionnaire and the data collected were analyzed using descriptive statistics (frequency and percentages) as well as multi-variate regression analysis. Result of the descriptive analysis shows that the mean age of the farmers was 64 years while 60% of the farmers had no access to formal education. Regression analysis revealed that farm size, variety of coffee, marketing channels, trading experience, membership of association, price satisfaction and selling method constituted major characteristic marketing factors influencing coffee marketing in the study area and they all affected coffee marketing at 1% significant level. Based on the findings, the study therefore recommended that efforts should be made to assess variety of coffee that is more preferred by the buyers. Also, farmers should be given incentives to increase their farm holdings for higher productivity.